Effect of Money Laundering on Foreign Remittances - Ashraf Faeq Mohamed; Tahani Mahdi Abbas (Journal of Madenat Alelem University College, 2021)
The phenomenon of money laundering is one of the most serious financial crimes whose effects are not confined to a specific area or environment, but extend to all political, social, moral and other negative effects of society. As banks are a major target for money launderers, Which are targeted by money launderers to conceal the sources of their money is illegal through the integration of these funds in the economy of the country or the smuggling of these funds outside the country through legal methods and here will be addressed to money laundering operations that are carried out through external remittance issued and received, N through the banking system. The researcher reached a number of conclusions and the most important, targeting money launderers for foreign and domestic remittances, whether through currency auction or internal transfers in money laundering, than other banking operations. The researcher also came up with a number of recommendations; the establishment of a department in the Office of AML / CFT, whose functions are to coordinate, follow up and supervise the entities that are in direct contact with the CBI in terms of the nature of the work such as customs and embassies, as foreign remittances are not carried out without the .presence of these entities.